2020
DOI: 10.1039/d0ra07840a
|View full text |Cite
|
Sign up to set email alerts
|

Co-digestion of microalgae with potato processing waste and glycerol: effect of glycerol addition on methane production and the microbial community

Abstract: Glycerol as an additional co-substrate enhanced methane yields by up to 128% when co-digestion with microalgae and potato waste.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 69 publications
0
4
0
1
Order By: Relevance
“…Most microalgae species have a low C/N ratio [33], and it is often associated with destabilization and reduced biomethane production in the AD process due to ammonia release and inhibition [110]. As a result, anaerobic digesters that solely process microalgae biomass operate at low organic loading rates (<2 g VS/L.d) to avoid ammonia build-up and subsequent process failure [77].…”
Section: Co-digestionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most microalgae species have a low C/N ratio [33], and it is often associated with destabilization and reduced biomethane production in the AD process due to ammonia release and inhibition [110]. As a result, anaerobic digesters that solely process microalgae biomass operate at low organic loading rates (<2 g VS/L.d) to avoid ammonia build-up and subsequent process failure [77].…”
Section: Co-digestionmentioning
confidence: 99%
“…Solé-Bundó et al [113] varied the microalgae to the co-substrate ratio (VS basis) in the AD from 100:0 to 75:25, 50:50, and 25:75, and reported 48, 140, and 223% higher biomethane production, respectively. Microalgae biomass has been successfully digested with other types of organic substrates, including food waste [114], animal manure [115], agro-industrial waste [116,117], glycerol (a by-product of the biodiesel industry) [110], and fat, oil, and grease (FOG) waste [118] to produce 19-500% higher biomethane. Recent studies have suggested pretreating microalgae biomass before co-digestion to achieve better biomethane yields.…”
Section: Co-digestionmentioning
confidence: 99%
“…Solé-Bundó et al (2019a) achieved a 60% increase in CH 4 yield applying a thermal pretreatment in the microalgae biomass and 15% after AcoD with WWTP residues (oil, grease, and fat). Zhang et al (2020) added glycerol to the AcoD of microalgae and potato processing residues and found an increase of more than 50% in CH 4 production. Assemany et al (2020) performed the…”
Section: Anaerobic Co-digestionmentioning
confidence: 99%
“…The high concentration of NH 3 in the digester affects the growth and metabolism of microorganisms and produces an accumulation of volatile fatty acids, which results in a decrease in biogas yield. This factor can also be supplied by choosing a good co-substrate and optimizing this C/N ratio [94].…”
Section: Effect Of Initial Conditionsmentioning
confidence: 99%